2013
DOI: 10.1371/journal.pone.0075722
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Wall Shear Measurements within the Developing Zebrafish Heart

Abstract: Physical forces can influence the embryonic development of many tissues. Within the cardiovascular system shear forces resulting from blood flow are known to be one of the regulatory signals that shape the developing heart. A key challenge in investigating the role of shear forces in cardiac development is the ability to obtain shear force measurements in vivo. Utilising the zebrafish model system we have developed a methodology that allows the shear force within the developing embryonic heart to be determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 21 publications
4
39
0
Order By: Relevance
“…Although the use of 2D moving-domain CFD modeling linked 3D hemodynamic forces (time and 2D plane) with mechanotransduction underlying AV valve morphogenesis, further increases in our computing capacity would enhance the use of 4D CFD (time and 3D space) to evaluate the hemodynamic microenvironment in the developing OFT. Nonetheless, the OFT WSS values obtained in our moving-domain CFD model system are consistent with previous studies (9).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the use of 2D moving-domain CFD modeling linked 3D hemodynamic forces (time and 2D plane) with mechanotransduction underlying AV valve morphogenesis, further increases in our computing capacity would enhance the use of 4D CFD (time and 3D space) to evaluate the hemodynamic microenvironment in the developing OFT. Nonetheless, the OFT WSS values obtained in our moving-domain CFD model system are consistent with previous studies (9).…”
Section: Discussionsupporting
confidence: 92%
“…These valves are structurally similar to mammalian valves, and the developmental cellular events of valvulogenesis are largely conserved among species (1). Previous studies have focused on the role of fluid shear stress in valve development; however, there remains a paucity of data elucidating the relative importance of contractile and hemodynamic shear forces in the outflow tract (OFT) of the developing zebrafish embryo (5,9), and the downstream signaling pathways and effects on VB valve development remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the conventional Particle Image Velocimetry (PIV) (Hove, 2006;Hove et al, 2003;Jamison et al, 2013), PTV has been demonstrated to capture the intracardiac blood flow (Yalcin et al, 2017), allowing for mapping the trajectories of individual dsRed-labeled blood cells from AVC to outflow track (OFT). While PIV provides high spatial resolution and detailed velocity profiles, PTV enables time-dependent tracking of each individual signal in a dynamic space.…”
Section: -D Vector Fields For Intracardiac Blood Flowmentioning
confidence: 99%
“…Embryos are imaged ventral-side up in a low gelling temperature agarose (Sigma Aldrich, Type VII-A, A0701), as previously described with an attempt to image along a crosssection aligned with the orientation of the heart (Johnson et al, 2015). The setup is illustrated in the each point in the cardiac cycle, a technique different from the sliding average previously used (Jamison et al, 2013;Johnson et al, 2013a). Therefore, the heart wall is removed, but slow moving red blood cells (RBCs) are not filtered from the images when performing flow calculations.…”
Section: Zebrafish Handling and Imagingmentioning
confidence: 99%